2007
DOI: 10.4028/www.scientific.net/msf.558-559.407
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Strain Path Effects on Static Recrystallisation in Hot Worked Aluminium Alloy AA5052 Using Forward and Reverse Torsion

Abstract: The effects of strain path reversal, using forward and reverse torsion, on the microstructure evolution in the aluminium alloy AA5052 have been studied using high resolution electron backscatter diffraction. Deformation was carried using two equal steps of forward/forward or forward/reverse torsion at a temperature of 300°C and strain rate of 1s-1 to a total equivalent tensile strain of 0.5. Sections of the as-deformed gauge lengths of both test specimens were then annealed at 400°C for 1 hour in a salt bath i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
0
0
Order By: Relevance
“…2, upon strain reversal, a significant drop of the flow stress level was observed in specimen X2 comparing to the test X1 without strain reversal. This phenomenon known as Bauschinger effect has been widely reported for different types of polycrystalline metallic materials and is believed to be associated with the annihilation of dislocations with opposite signs after strain reversal [2]. In the present study, the difference between flow stresses is about 20MPa.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…2, upon strain reversal, a significant drop of the flow stress level was observed in specimen X2 comparing to the test X1 without strain reversal. This phenomenon known as Bauschinger effect has been widely reported for different types of polycrystalline metallic materials and is believed to be associated with the annihilation of dislocations with opposite signs after strain reversal [2]. In the present study, the difference between flow stresses is about 20MPa.…”
Section: Resultssupporting
confidence: 50%
“…Previous studies have revealed that this strain path can affect the recrystallisation kinetics of stainless steels [1] and aluminium alloys [2] as well as the kinetics of spheroidisation of titanium alloys [3]. For microalloyed steels, it has been reported the strain reversal retards the recrystallisation and Nb(C,N) precipitation kinetics [4].…”
Section: Introductionmentioning
confidence: 99%